Atrial myopathy: a pathogenic mechanism linking atrial fibrillation and ischemic stroke - Kahadi, Cik; Rizal, Ardian (Universitas Brawijaya, 2025)
Atrial myopathy (AM) has become a topic of study for many years. Atrial Myopathy is characterized as